Occupational health morbidities and associated socio-demographic variables among street sweepers in a metropolitan city - Mishra, Tuhina; Sukhsohale, Neelam; Mankeshwar, Ranjit (International Journal Of Community Medicine And Public Health, 2020)
BACKGROUND- In India, the traditional culture has stigmatized street sweeping as a filthy and lowly occupation. The medical problems of these workers are further compounded by various socioeconomic factors such as poverty, lack of education, poor housing conditions and poor diet. The objective of the current study was to assess the socio demographic profile of the street sweepers, the morbidities prevalent amongst them and to establish an association between socio demographic variables and various morbidities. METHODS- A cross sectional questionnaire based epidemiological study was carried out ,after taking written consent, amongst 100 street sweepers belonging to age group of 18-60 years in South Mumbai under E ward of Brihanmumbai Municipal Corporation for a period of 2 months. RESULTS- Skin problems (91%) followed by musculoskeletal disorders (88%) were the most common morbidities observed amongst street sweepers predominantly in males belonging to the age group of 40-50 years. The prevalence of anemia was found to be relatively higher in females with low socio economic background (6.7%). It was also observed that greater the duration of services, more was the risk of morbidities like musculoskeletal disorders (88.5%), respiratory disorders (11.5%), hypertension (6.4%) and cardiovascular disorders (1.3%). CONCLUSION- The most common morbidities observed were skin problems ( 91%) and musculoskeletal disorders (88%) predominantly in males belonging to age group 40-50 years. Anemia was more common in females . Additionally, illiteracy was a risk factor for respiratory symptoms (14.7%). KEYWORDS- Occupational health, Health hazards, Street sweepers,